2011
DOI: 10.1029/2010jf001891
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian network to predict coastal vulnerability to sea level rise

Abstract: [1] Sea level rise during the 21st century will have a wide range of effects on coastal environments, human development, and infrastructure in coastal areas. The broad range of complex factors influencing coastal systems contributes to large uncertainties in predicting long-term sea level rise impacts. Here we explore and demonstrate the capabilities of a Bayesian network (BN) to predict long-term shoreline change associated with sea level rise and make quantitative assessments of prediction uncertainty. A BN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 102 publications
1
115
0
1
Order By: Relevance
“…1) similar to those used in previous coastal vulnerability studies (e.g. Thieler, 1999;Coelho et al, 2006;Gutierrez et al, 2011). The causal relationships (black arrows, Fig.…”
Section: Bayesian Network Designmentioning
confidence: 92%
See 3 more Smart Citations
“…1) similar to those used in previous coastal vulnerability studies (e.g. Thieler, 1999;Coelho et al, 2006;Gutierrez et al, 2011). The causal relationships (black arrows, Fig.…”
Section: Bayesian Network Designmentioning
confidence: 92%
“…By evaluating the model behaviour using from one to four variables, the geomorphology was identified as the most important model parameter determining coastal evolution trends. In a study of the US Atlantic Coast, Gutierrez et al (2011) concluded that sea-level rise was the primary model parameter affecting shoreline stability, which encourages future study of the differences between and the broad applicability of such predictive models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar application, Mondini et al (2013) map and classify landslides in southern Taiwan using a Bayesian framework. Examples from other areas of geomorphology include Gutierrez et al (2011), who 456 A. P. Valentine and L. M. Kalnins: An introduction to learning algorithms use a Bayesian network to predict shoreline evolution in response to sea-level change, and Schmelter et al (2011), who use Bayesian techniques for sediment transport modelling.…”
Section: Bayesian Inferencementioning
confidence: 99%